2021
DOI: 10.1007/s11433-021-1712-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic-photonic cavity for high-efficiency single-photon blockade

Abstract: The generation and manipulation of single photons are crucial in advanced quantum technologies, such as quantum communication and quantum computation devices. High-purity single photons can be generated from classical light using the single-photon blockade (1PB). However, the efficiency and purity are exclusive in 1PB, which hinders its practical applications. Here, we show that the resonantly coupled plasmonic-photonic cavity can boost the efficiency of single-photon generation by more than three orders of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Meanwhile, quantum light-matter interactions, for example see Refs. [14][15][16][17][82][83][84][85][86][87][88][89], have been the subject of intense theoretical and practical interest. Our method can serve as a robust and valuable tool in this field, when plasmonic effects in mesoscopic metal nanostructure is exploited.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, quantum light-matter interactions, for example see Refs. [14][15][16][17][82][83][84][85][86][87][88][89], have been the subject of intense theoretical and practical interest. Our method can serve as a robust and valuable tool in this field, when plasmonic effects in mesoscopic metal nanostructure is exploited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that the atom-photon quasi-bound state (qBS) can form in this kind of dissipation-mediated cQED system with ω a = ω c and 14) by finding the condition of a purely real eigenvalue, which is shown to yield the highest single-photon efficiency [31,32]. In order to achieve the best 1PB performance, in the following study we will apply the aforementioned condition of atom-photon qBS.…”
Section: Effective Atom-photon Interaction and Chiralitymentioning
confidence: 99%
“…Furthermore, one can obtain the LDOS of target nanophotonic structure that owns desirable quantum effects of EPs for EM design. This is important for structure optimization, especially for these consisting of absorbing and dispersing medium like the plasmonicphotonic cavity [76][77][78][79], where the coupling rate between cavity modes is hard to evaluate, contract to the ES microcavity studied in this work. On the other hand, the quantum-optics properties of a given nanophotonic structure are predictable, by parametrizing the extended cascaded QME (Eq.…”
Section: Is the Spectral Density Of Es Microcavity The Correlation Fu...mentioning
confidence: 99%